الأعمال الطبية الحديثة بين الأحكام الفقهية والقانون الإندونيسي (دراسة مقاصدية في طفل الأنابيب و منع الحمل و زراعة الأعضاء) - Fajar, Ricky (Profetika Jurnal Studi Islam, 2016)
A The purpose of this study is to describe the surgery of modern medicine in in vitro fertilisation (IVF), contraception and organ transplants between Indonesian  regulation, it’s seen from the viewpoint of "maqosidsyareahIslamiyah," and I started with definition of the surgery of modern medical, legal jurisprudence, legislation and maqosidsyareah, then an explanation of the applicable regulations, and laws maqosid of the review that took place in Indonesian society.in this study I used qualitative research and literature, by reading medical books required and books of fiqh contemporary for completeness, then I used the method of comparison, between the opinions of medicine and jurisprudence, and method of conclusions by looking at events that hit with a solution from the point of view of maqosid to keep human emergency law, of keeping religion, life, property, intellect, and descent, with the words of scholars in the application maqosidsyareah. Conclusions of law IVF, including temporary because of sterility of husband and wife, and this is permitted, other than one of the two or lease womb is forbidden like adultery, although there is a need and treat infertile, thenvasectomy and tubal ligation including emergency contraception is forever, the rest, including the need is temporary, except spiral, modern gelding, and implants that could be forever, then autograft, isograft, and allograft included in the emergency laws if they can help the lives, while the rest, including the need if it’s proven to be beneficial. Tujuan tesis ini menjelaskan operasi medis modern dalambayi tabung, kontrasepsi dan transplantasi organ antara undang undang Indonesia dan hokum fiqih, dilihat dari sudut pandang “maqosid syareah islamiyah”, dan saya mulai dengan pengertian operasi medis modern, hukum fiqih, undang-undang dan maqosid syareah, kemudian penjelasan tentang ketentuan yang berlaku, serta hokum maqosid dari tinjauan yang terjadi di masyarakat Indonesia.Saya berpedoman dalam penelitian ini dengan studi kualitatif dan kepustakaan, dengan membaca buku kedokteran yang diperlukan dan buku fiqih kontemporer untuk kelengkapanya, kemudian saya gunakan metode perbandingan,antarapendapat kedokteran dan fiqih, dan metode kesimpulan dengan melihat kejadian yang melanda dengan solusi dari sudut pandang maqosid untuk menjaga hukum darurat manusia, dari menjaga agama, jiwa, harta, akal, dan keturunan, dengan perkataan ulama dalam penerapan maqosid syareah. Kesimpulan dari hukum bayi tabung, termasuk kebutuhan dengan sebab mandulnya suami istri, dan ini dibolehkan, selain salah satu dari keduanya atau sewa rahim haram mirip zina,walau ada kebutuhan dan mengobati mandul, kemudian vasektomi dan tubektomi termasuk kontrasepsi darurat bersifat selamanya, sisanya termasuk kebutuhan bersifat sementara, kecuali spiral, kebiri modern, dan implant yang bisa bersifat selamanya, kemudian autograft, isograft, dan allograft termasuk dalam hukum darurat jika mampu menolong nyawa, adapun sisanya termasuk kebutuhan jika terbukti bermanfaat. الخلاصة: إستهدف هذا البحث بيان الأعمال الطبية الحديثة في أطفال الأنابيب ومنع الحمل وزراعة الأعضاء بين القانون الإندونيسي والأحكام الفقهية،من جانب حكم "مقاصد الشريعة الإسلامية"، وابتدأت في هذا الجهد بمفهوم العملية الطبية الحديثة، ثم مفهوم الأحكام الفقهية و القانون الإندونيسي و مقاصد الشريعة منها.ثم بيان الضوابط الطبية والفقهية فيها، ثم الأحكام المقاصدي بنظر إلى الواقع في مجتمع إندونيسي.وقد إعتمدت الدراسةبالبحث النوعي،وإعتمدت بدراسة المكتبية بقرآءة الكتب الطبية المحتاجة والكتب الفقهية المعاصرة لإتمام المعلومات.كما إستخدمت المنهج المقارن,وذلك بمقارنة بين موقف الطب و الفقه.والمنهج الإستنباطي بنظر إلى الواقعة المنتشرة الذي محل تحليلها من جانب المقاصد لحفظ ضرورة الناس، من حفظ الدين،والنفس،والمال،والعقل والنسل مع أقوال العلماء في تطبيق المقاصد الشريعة. ونتيجة المقاصد في طفل الأنابيب حكمه داخل في الحاجية بين الزوجين بسبب العقم وذلك جائز فعلا،أما من غير أحدهما أو مع إستئجار الأرحام فهذا حرام وشبه زنا ولو بوجود حاجة ولعلاج العقم، ثم فاسكتومي وتوبكتومي من نوع منع الحمل الضروري المؤبد،وبقية الأنواع داخل في حكم حاجية للمؤقتإلاّ اللولب،والخصاء الحديث،والهورمونات الجلدية الإمتصاص في نوع حاجية دائمة،ثم غريسة ذاتية متمالثة ومتباينة من الضرورة حكما إن حصلت إنقاذ الحياة وبقية الأنواع في الغريسة حكمه كالحاجية إذا تبينت الفائدة.